An Automatic Wild Life Tracking System Using GPS and WSN - Vilasrao Nalawade, Rushikesh; Ramesh Bongale, Priya; Kalidas Deshmane, Utkarsh; Potdar, Deepali (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Every living creature on this earth has equal importance in the ecosystem. But nowadays life of wild animals is in danger. Wild animals used to move freely in the forest or in the jungle. If any accident happens to them in the forest, physical injury or any disease may cause even death of animals in the forest. In such situations we cannot find out exact location of animal every living creature on this earth has equal importance in the ecosystem. To avoid such problems in the finding exact geographical location of animal in the jungle, national park or in wildlife reserves, wildlife animal tracking system is used. It also reduces the rising fatalities in a human animal conflict and also drastically reduces zoo thefts.
Keywords: GPS technology; human-animal conflict; monitoring; tracking wild animals; location